Investigation of Corrosion Behavior of Low Carbon Steel Oil Pipelines - Alsultani, Dr.Kadhim F.; Jasem, Dr.Ahmed A.; Ali, Duaa Amer (Journal of Petroleum Research and Studies, 2017)
The research aims at investigating the corrosion behavior of low Carbone steel pipelines welds and mechanical properties of weldment . The corrosion behavior was investigated in crude oil and water extraction from oil to study the effect of water chemistry on corrosion employing electrochemical and weight loss measurements. Corrosion and erosion-corrosion have important role in oil fields especially in oil pipelines . The experimental work tests of erosion- corrosion were done using special device which was designed and manufactured according to (G 73) ASTM . The work tests were achieved using traditional weight loss technique to measure weight loss rates in (mpy) Unit, the tests above were done in pumped media and pumped media had constant pressure of 1 bar, flow rate Q = 36 L/min, temperature ≈25 ºC and pH = 6.56 for erosive-corrosive media. Weight loss method was used in which test specimens of carbon steel, with a known weights, were immersed in the oil for a total exposure time of 60 days. The weight loss was measured at an interval of 10 days, whereas in water specimens immersed for 30 day at an interval 2 days. The corrosion rate was determined using (mpy) unit. Metallographic observations and micro-hardness measurements were also performed on specimens taken from the parent metal, heat affected zone and weld metal. The obtained results clearly indicate a degradation of the mechanical properties of steel welds.